2012
DOI: 10.1371/journal.pntd.0001517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Forms of Chikungunya in Gabon, 2010

Abstract: BackgroundChikungunya virus (CHIKV) has caused multiple outbreaks in tropical and temperate areas worldwide, but the clinical and biological features of this disease are poorly described, particularly in Africa. We report a prospective study of clinical and biological features during an outbreak that occurred in Franceville, Gabon in 2010.Methodology/Principal FindingsWe collected, in suspect cases (individuals presenting with at least one of the following symptoms or signs: fever, arthralgias, myalgias, heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 44 publications
6
45
3
3
Order By: Relevance
“…This is not surprising since all the patients in our study were initially diagnosed with clinical dengue on presentation. Although other studies have found varying values for different combinations of symptoms, 41,42 we did not find any combination of symptoms that had sufficiently high sensitivity and specificity in diagnosing either dengue or chikungunya (Table 5 and 6). The combination of fever, joint pain, and skin rash showed a high sensitivity but low specificity (Table 5) in diagnosing chikungunya infection, whereas the combination of fever, joint pain, and muscle/body pain had a high sensitivity but low specificity (Table 6) in diagnosing dengue.…”
Section: Discussioncontrasting
confidence: 68%
“…This is not surprising since all the patients in our study were initially diagnosed with clinical dengue on presentation. Although other studies have found varying values for different combinations of symptoms, 41,42 we did not find any combination of symptoms that had sufficiently high sensitivity and specificity in diagnosing either dengue or chikungunya (Table 5 and 6). The combination of fever, joint pain, and skin rash showed a high sensitivity but low specificity (Table 5) in diagnosing chikungunya infection, whereas the combination of fever, joint pain, and muscle/body pain had a high sensitivity but low specificity (Table 6) in diagnosing dengue.…”
Section: Discussioncontrasting
confidence: 68%
“…Chikungunya infection is a neglected tropical disease caused by the Chikungunya virus (CHIKV), an arthropod-borne virus belonging to the alphavirus group [1,2]. The clinical manifestations of CHIK are well defined [1].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of CHIK are well defined [1]. The infection can be diagnosed by serology to detect IgG and/or IgM.…”
Section: Introductionmentioning
confidence: 99%
“…In neonates, CHIKF can be accompanied by convulsions, peripheral cyanosis, podalic edema, and epithelial vesicular lesions that eventually dry and scale 35,36 . This disease is usually considered benign in children 37 .…”
Section: Acute Phasementioning
confidence: 99%
“…Other less common symptoms include neuropathy, cerebral disorder, neurosensory deficiency, burning mouth syndrome, paresthesia, cubital tunnel syndrome, gastrointestinal disorders, exanthema, pruritus, bursitis, and synovitis 28,36,44,[47][48][49] .…”
Section: Chronic Phasementioning
confidence: 99%